Asymmetry during preseason Functional Movement Screen testing is associated with injury during a junior Australian football season. Issue 7 (July 2017) - Chalmers, Samuel; Fuller, Joel T.; Debenedictis, Thomas A.; Townsley, Samuel; Lynagh, Matthew; Gleeson, Cara; Zacharia, Andrew; Thomson, Stuart; Magarey, Mary
Abstract: Objectives: The Functional Movement Screen (FMS) is a popular screening tool, however, the postulated relationship between prospective injury and FMS scoring remains sparsely explored in adolescent athletes. The aim of the study was to examine the association between pre-season FMS scores and injuries sustained during one regular season competition in elite adolescent Australian football players. Design: Prospective cohort study. Methods: 237 elite junior Australian football players completed FMS testing during the late pre-season phase and had their weekly playing status monitored during the regular season. The definition of an injury was 'a trauma which caused a player to miss a competitive match'. Results: The median composite FMS score was 14 (mean = 13.5 ± 2.3). An apriori analysis revealed that the presence of ≥1 asymmetrical sub-test was associated with a moderate increase in the risk of injury (hazard ratio = 2.2 [1.0–4.8]; relative risk = 1.9; p = 0.047; sensitivity = 78.4%; specificity = 41.0%). Notably, post-hoc analysis identified that the presence of ≥2 asymmetrical sub-tests was associated with an even greater increase in risk of prospective injury (hazard ratio = 3.7 [1.6–8.6]; relative risk = 2.8; p = 0.003; sensitivity = 66.7%; specificity = 78.0%). Achieving a composite score of ≤14 did not substantially increase the risk of prospective injury (hazard ratio = 1.1 [0.5–2.1]; p = 0.834). Conclusions: Junior Australian football players demonstrating asymmetrical movement during pre-season FMS testing were more likely to sustain an injury during the regular season than players without asymmetry. Findings suggest that the commonly reported composite FMS threshold score of ≤14 was not associated with injury in elite junior AF players.